Factor XIII Deficiency due to a Leu660Pro Mutation in the Factor XIII Subunit-a Gene in Three Unrelated Palestinian Arab Families - Inbal, Aida; Yee, Vivien C; Kornbrot, Nurit; Zivelin, Ariella; Brenner, Benjamin; Seligsohn, Uri (Thrombosis and Haemostasis, 1997)
In this report we describe the molecular basis of FXIII a-subunit deficiency in three unrelated Palestinian Arab families. In three patients representing each family two substitutions were identified in exon 14 on both alleles: C to G change resulting in a Gln651Glu substitution (a previously described polymorphism) and a T to C transition causing Leu660Pro substitution. The latter is a new mutation which creates a restriction site for FnuDII enzyme. Restriction analysis performed in members of the three families clearly distinguished between severely affected patients, obligate carriers and unaffected subjects. A population survey failed to detect the mutation among 250 Jewish individuals but did detect two heterozygotes among 300 Arabs suggesting a 0.0033 frequency for the Pro660 allele in this population. In two out of the three families the Pro660 allele was linked to allele 5 of the 5’ short tandem repeat polymorphism within the FXIII a-subunit gene suggesting that the mutation might have occurred at least twice. cDNA obtained from mRNA isolated from patients’ platelets and monocytes appeared similar in size to that of normal control indicating that the Leu660Pro mutation does not affect mRNA synthesis. Computer modeling based on cristallographic studies of the a-subunit of factor XIII predicted that the mutant protein is expected to misfold into a structure which is either unstable or susceptible to degradation.